2023
DOI: 10.1108/bepam-12-2022-0195
|View full text |Cite
|
Sign up to set email alerts
|

Prospects, drivers of and barriers to artificial intelligence adoption in project management

Abstract: PurposeThe rise of artificial intelligence (AI) and differing attitudes towards its adoption in the building and environment (B&E) industry has an impact upon whether companies can meet changing demand and remain relevant and competitive. The emergence of Industry 4.0 technologies, coupled with the repercussions of COVID-19, increases the urgency and opportunities offered that companies must react to, as disruptive technologies impact how project management (PM) professionals work and necessitate acquisiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…In addition, adequate training is also required for companies that intend to adopt such technology. This finding is in line with the result of other study (Shang et al 2023) which explains that lack of knowledge on AI technologies and applications and lack of skilled and trained employees are two of several other barriers to the adoption of AI in the scope of project management. This is due to the use of AI systems that are still relatively new in their industry where familiarity with the use of AI itself is still lacking.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, adequate training is also required for companies that intend to adopt such technology. This finding is in line with the result of other study (Shang et al 2023) which explains that lack of knowledge on AI technologies and applications and lack of skilled and trained employees are two of several other barriers to the adoption of AI in the scope of project management. This is due to the use of AI systems that are still relatively new in their industry where familiarity with the use of AI itself is still lacking.…”
Section: Discussionsupporting
confidence: 91%
“…This is due to the requirement of each of these parties, which does not require complex technology and is sufficient to be completed with existing technological resources. These two factors are in line with the findings of a study (Shang et al 2023) where the study showed that the lack of need for adoption and lack of support from project stakeholders are several things that become obstacles in the adoption of AI technology in the scope of project management. The last factor influencing the decision to use this technology is the limited resources available, specifically financial resources.…”
Section: Discussionsupporting
confidence: 87%
“…More so, the successfully prototyped use cases, such as Cantador et al (2021) open data chatbot and AI Singapore's Ask Jamie virtual assistant (Ojeda, 2021;Shang et al, 2023), exemplify how generative AI models can collect and convey multifaceted governance information in easily understandable formats. By abstracting away complexity through fluent dialogues, these systems democratise access to the policy sphere, fostering a more participatory dynamic.…”
Section: Generative Ai and Civic Engagementmentioning
confidence: 97%
“…AI-powered tools can facilitate better communication among team members by providing real-time updates and predictive insights, leading to more coordinated efforts. Machine learning algorithms can tailor solutions based on specific project needs, ensuring a more targeted approach in project management [8,38]. Moreover, in projects with varying work conditions, AI aids in identifying early warning signs of potential accidents during execution.…”
Section: Successful Project Implementation Using Aimentioning
confidence: 99%